Centro modal de transferencia Meandro del Say como articulador entre la sabana de occidente (2018)
Mobility in Bogota both at district and regional level, during the last updates, has not been the best result, because the capital of the country has grown now and this growth has brought the need to expand the infrastructure of uses and the housing, however, the infrastructure has not been improved and the traffic in the region does not have the scope of the necessary routes for the mobility of the users; The modal transfer project Meandro del Say is a vision of the improvement of mobility in the capital of Colombia, Bogotá and its surrounding municipalities to the west (Mosquera, Madrid, Funza and Facativá) With a hybrid of complementary services, the application of routes intermunicipal transport and the integration of existing means of transport (counting on the revitalization of the commuter train), the purpose of being an efficient transport node, providing the best transport in the region